ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA DITINJAU DARI KECEMASAN MATEMATIKA [ANALYSIS OF STUDENTS' MATHEMATICAL REPRESENTATION ABILITY IN TERMS OF MATH ANXIETY] - Nur Lisa Andriani; Nur Fauziyah (JOHME: Journal of Holistic Mathematics Education)
The purpose of this research is to describe the profile of students' mathematical representation ability in terms of math anxiety. This research method is descriptive qualitative method. The research was conducted at SMAN 1 Manyar with the research subjects being 3 class X students, consisting of students with low, medium, and high levels of math anxiety. There are two instruments in this study, namely a math anxiety questionnaire and mathematical representation ability test questions. Data analysis techniques used in this study consist of data reduction, data presentation, and conclusion drawing. The results of the research data showed the profile of mathematical representation ability (1) subjects with “low” math anxiety level had good visual representation ability, but still lacking in symbolic and verbal representation, (2) Subjects with “medium” math anxiety level had quite good visual mathematical representation ability, but still lacking in symbolic and verbal representation (3) subjects with “high” math anxiety level did not fulfill all of the three indicators of mathematical representation ability.